Pengembangan Media Pembelajaran Aplikasi Android Berbasis Powerpoint Untuk Mengingkatkan Kemampuan Visual Matematis Siswa - Lilis Anastasia Purba; Glory Indira D. Purba (Lembaga Pengembangan Kinerja Dosen, 2023)
The use of learning media that is less than optimal is the basis of this research with the aim of developing learning media for Android applications and knowing the process of student answers. This type of research is development research with a model adapted from Borg and Gall with a sample of class VIII-2 students of Santa Maria Private Middle School Medan, totaling 25 people. From the results of the study, it was obtained (1) the quality of the developed learning media met the valid, practical, and effective categories with an assessment by media experts of 3.82 and material experts of 3.87, practicality from the student response with a score of 3.61 and the teacher's response with a score of 4, and the effectiveness of classical student learning completeness reaches 92% of students and an n-gain score of 0.62 which means an increase in mathematical visual abilities is included in the moderate category. (2) The process of student answers shows that students have been able to identify problems, understand problems, generalize patterns and explain what is obtained, which means that students have fulfilled each indicator of mathematical visual ability, namely looking, seeing, imagining, showing and telling.